EVALUASI MANAJEMEN DOKUMEN REKAM MEDIS DI FILING AKTIF RUMAH SAKIT SWASTA KABUPATEN SEMARANG - Bobby Anggara Laksana; Retno Astuti Setijaningsih (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Missfile can inhibit medical services provided to patients without information about history. From the initial survey, it found 90 missile incidents (4.7%) from 2000 medical record documents, the second survey found 578 incidents from 7000 medical record documents with 9.0% missfile. This study aims to identify the medical records management in the outpatient filing section of The Private Hospital, Semarang Regency in 2019. This research is a mix methode study. Data collection by observation and interview methods with a cross-sectional approach. The research subjects were 3 filing officers. The research objects to the management of medical record documents in the outpatient filing section. The research instrument used in this research were interview and observation guidelines.The number of polyclinics at The Private Hospital in Semarang Regency is 20 polyclinics. There should be a submission terminal so staff will not be tired. The hospital management facilities were adequate but have not been properly utilized by the officers, the officers should use these facilities to facilitate document tracking. The Hospital should make a policy regarding the management of medical record documents and use colour codes on the documents so that the staff can understand and carry out their duties properly.Key Word : medical record management, storage systems, management standards